The Penetration Of Mobile Money In Ghana:Opportunities And Threats - Thomas Clifford Amoah (knust, 2025)
I Give All The Glory To GOD Almighty Who Through Christ Jesus Granted Me Life, Opportunity, Strength And Resources To Accomplish This Thesis. I Also Wish To Express My Deepest Appreciation To My Supervisor, Dr. Oscar Akottey, Who Continually Encouraged Me. Without His Guidance And Support This Work Would Have Not Been Possible. I Would Like To Thank The Bankers Who Took Time From Their Busy Schedules To Be Interviewed And Their Friendliness. Finally, To My Family Especially, My Dad And Mom, Mr. & Mrs. Daniel Sarporng And My Entire Siblings For Their Support And Prayers.